2020
DOI: 10.1101/2020.04.19.20054262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary post-mortem findings in a large series of COVID-19 cases from Northern Italy

Abstract: Importance. The analysis of lung tissues of patients with COVID-19 may help understand pathogenesis and clinical outcomes in this life-threatening respiratory illness. Objective.To determine the histological patterns in lung tissue of patients with severe COVID-19.Design and participants. Lungs tissues of 38 cases who died for COVID-19 in two hospital of Northern Italy were systematically analysed. Hematoxylin-eosin staining, immunohistochemistry for the inflammatory infiltrate and cellular components, electro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
120
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 10 publications
10
120
0
9
Order By: Relevance
“…A similar observation was recently described [18]. Angiopathic microvascular occlusion has been proposed as the underlying mechanism [19].Another recent study showed brin thrombi of small arterial vessels less than 1 mm in diameter in 33 of 38 patients with high D-dimer levels [20]. Increased D-dimer levels in our patients with PDs are supportive of these observations.…”
Section: Discussionsupporting
confidence: 90%
“…A similar observation was recently described [18]. Angiopathic microvascular occlusion has been proposed as the underlying mechanism [19].Another recent study showed brin thrombi of small arterial vessels less than 1 mm in diameter in 33 of 38 patients with high D-dimer levels [20]. Increased D-dimer levels in our patients with PDs are supportive of these observations.…”
Section: Discussionsupporting
confidence: 90%
“…Post-mortem examinations of COVID-19 patients reveal the aftermath of these disease dynamics: diffuse alveolar damage, multi-organ infiltration of lymphocytes and alveolar macrophages [1,7,15,16], and pneumocyte hyperplasia and peribronchiolar metaplasia in the epithelium resembling adenocarcinomas [15,16,17]. These morphological findings suggest local and systemic activation and infiltration of inflammatory immune cells that may contribute to the inflammatory injuries of the respiratory system consistent with ARDS phenotypes in severe COVID-19 [15].…”
Section: Introductionmentioning
confidence: 92%
“…Significant transcriptional changes in cells of the BALF were abundant in all cell types with the exception of plasma cells. We first directed our attention to the epithelium, where substantial morphological damage and histological atypia were observed in deceased COVID-19 patients [1,7,15,17,16]. At the level of individual gene regulation, we first noted a surprisingly strong significant upregulation of FOS and JUN, which code for proteins implicated in the development of cancer ( Figure 3A).…”
Section: Pathway-level Regulation Differentiates Mild and Severe Covimentioning
confidence: 99%
“…[6][7][8] Despite these clinical observations, there has been relatively little clinicopathologic correlation with the post-mortem findings in COVID-19 which to date have generally focused on the pulmonary histology of diffuse alveolar damage. [9][10][11][12] Herein we report the first cases of SARS-CoV-2 associated HLH diagnosed post-mortem using histologic, clinical and laboratory criteria.…”
Section: Introductionmentioning
confidence: 99%